The Study of Air Pollution of Metal Elements in Hanoi, Hung Yen and Dong Nai Using Barbula Indica Moss - Khiem, L. H.; Quan, V. D.; Trinh, T. T. M.; Frontasieva, M. F.; Tien, D. P. T.; Nam, L. D.; Mai, N. N.; Quyet, N. H.; Hong, K. T.; Son, N. A.; et al. (Communications in Physics, 2019)
Air pollution in Vietnam, especially the pollution caused by metal elements are more severe due to the rapid growth of industrialization. The study of air pollution caused by metals elements is a hard and expensive work. Develoment of the simple and cheap methods for studying metal pollution in the air is being carried out in many countries of the world. In this paper, we used Barbula Indica moss for studying heavy metal pollution in the air in Hanoi, Hung Yen and Dong Nai provinces and the obatined results will be presented.